Clinical and economic outcomes associated with the use of fluticasone propionate 250 mcg and salmeterol 50 mcg combination versus tiotropium bromide 18 mcg as initial maintenance treatment for chronic obstructive pulmonary disease in managed care. (3rd June 2018) - Bell, Christopher F.; Coutinho, Anna D.; Farrelly, Eileen; Lokhandwala, Tasneem; Landsman-Blumberg, Pamela
Abstract: Aims: To examine the clinical and economic outcomes associated with the use of long-acting bronchodilators for initial maintenance treatment of chronic obstructive pulmonary disease (COPD) by analyzing health insurance claims data in the US. Methods: A retrospective, observational, matched cohort study used health insurance claims data (January 2008 to June 2013) to assess COPD-related outcomes for subjects aged ≥40 years. Subjects were assigned to a study cohort according to the first observed prescription fill for a long-acting bronchodilator (fluticasone propionate 250 mcg/salmeterol 50 mcg [FSC] or tiotropium bromide 18 mcg [TIO]). The analysis period for each subject comprised a 1-year pre-index date and 1-year post-index date. Primary outcome measure was total COPD-related costs per-patient per-year (PPPY) during the follow-up period. Secondary outcome measures included COPD-related exacerbations and the components of COPD-related costs. Results: Overall, 24, 040 subjects were identified; the analysis sample consisted of 19, 090 subjects (9, 545 per cohort) with no significant differences between cohorts. Mean COPD-related total costs PPPY were numerically lower among the FSC cohort; however, the difference was not statistically significant (2, 224 [±4, 108] vs 2, 352 [±3, 721], p = .057). There was no difference between cohorts for COPD-related medical costs ( p = .894). COPD-related pharmacy costs were significantly, yet modestly, lower in the FSC cohort compared with the TIO cohort (1, 160 [±1, 106] vs 1, 275 [±1, 110], p < .001). There were no statistically significant differences in the rate or number of exacerbations between the matched cohorts. Limitations: While propensity scoring achieved balance in baseline characteristics, some residual confounding unobserved in the database may be present. Conclusions: Few clinical and economic differences between subjects initiating maintenance therapy with FSC or TIO were observed.